Toxic heavy metals of agricultural products in developing countries and its human health risk assessment: A study from Iran - Ali Amarloei; Heshmatollah Nourmoradi; Shahrokh Nazmara; Mohsen Heidari; Fazel Mohammadi-Moghadam; Sajad Mazloomi (Heliyon)
Food toxicity through heavy metals, particularly from cereal consumption, poses significant threats to human health. This study studied various toxic heavy metals (Pb, As, Cr, Cd, Co, Hg, and Ag) in cereal products and their human health risk assessment in Ilam province, Iran.This study analyzed 30 samples of the most commonly cultivated cereals (wheat, rice, corn, pea, and lentil) in Ilam province. ICP-MS was used to measure the concentrations of selected toxic heavy metals.According to the obtained results, only the rice samples had concentrations of As and Pb that exceeded Iran's national standards. Monte Carlo simulation showed that the 95th percentile (P95th) values of hazard quotient (HQ) for As in wheat and rice, Hg in wheat, and Pb in rice were above 1. Moreover, P95th values of incremental lifetime cancer risk (ILCR) for As in wheat and rice were above 10−4The findings showed that the consumption of wheat and rice in the Ilam province was a potential source of exposure to As, Pb, and Hg. This study recommends the necessity of monitoring heavy metals in cereal products to protect human health.